Fitness of calves born from in vitro-produced fresh and cryopreserved embryos - Gómez, Enrique; Murillo, Antonio; Carrocera, Susana; Pérez-Jánez, Juan José; Benedito, Jose Luis; Martín-González, David; Gimeno, Isabel (Frontiers in Veterinary Science, 2022)
In cattle, vitrified/warmed (V/W) and frozen/thawed (F/T), in vitro-produced (IVP) embryos, differ in their physiology and survival from fresh embryos. In this study, we analyzed the effects of embryo cryopreservation techniques on the offspring. IVP embryos cultured with albumin and with or without 0.1% serum until Day 6, and thereafter in single culture without protein, were transferred to recipients on Day 7 as F/T, V/W, or fresh, resulting in N = 24, 14, and 13 calves, respectively. Calves were clinically examined at birth, and blood was analyzed before and after colostrum intake (Day 0), and subsequently on Day 15 and Day 30. On Day 0, calves from V/W and F/T embryos showed increased creatinine and capillary refill time (CRT) and reduced heartbeats. Calves from F/T embryos showed lower PCO2, hemoglobin, and packed cell volume than calves from V/W embryos while V/W embryos led to calves with increased Na+ levels. Colostrum effects did not differ between calves from fresh and cryopreserved embryos, indicating similar adaptive ability among calves. However, PCO2 did not decrease in calves from V/W embryos after colostrum intake. Serum in culture led to calves with affected (P < 0.05) temperature, CRT, HCO3-, base excess (BE), TCO2, creatinine, urea, and anion gap. On Day 15, the effects of embryo cryopreservation disappeared among calves. In contrast, Day 30 values were influenced by diarrhea appearance, mainly in calves from V/W embryos (i.e., lower values of TCO2, HCO3-, and BE; and increased glucose, anion gap, and lactate), although with no more clinical compromise than calves from fresh and F/T embryos. Diarrhea affected PCO2 and Na+ in all groups. Embryo cryopreservation, and/or culture, yield metabolically different calves, including effects on protein and acid–base metabolism.